2022
DOI: 10.1121/10.0009801
|View full text |Cite|
|
Sign up to set email alerts
|

Psychoacoustic modelling of rotor noise

Abstract: The aviation sector is rapidly evolving with more electric propulsion systems and a variety of new technologies of vertical take-off and landing manned and unmanned aerial vehicles. Community noise impact is one of the main barriers for the wider adoption of these new vehicles. Within the framework of a perception-driven engineering approach, this paper investigates the relationship between sound quality and first order physical parameters in rotor systems to aid design. Three case studies are considered: (i) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…With respect to the psychoacoustic performance, we performed a comprehensive analysis of the improved Zwicker's psychoacoustic metrics. While several previous studies [24,26,43] pointed out that the human response to drone noise highly depends on the dominant factor of loudness metrics, in this study, it is verified that the loop-type propellers can markedly reduce the mid-range-frequency tonal noise at the cost of broadband noise in high-frequency range, which is beneficial for the loudness of low weighting in the high-frequency range. Gwak et al [24] also reported that the fluctuation strength and the sharpness are a notable feature observed in the annoyance of UAV noise.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…With respect to the psychoacoustic performance, we performed a comprehensive analysis of the improved Zwicker's psychoacoustic metrics. While several previous studies [24,26,43] pointed out that the human response to drone noise highly depends on the dominant factor of loudness metrics, in this study, it is verified that the loop-type propellers can markedly reduce the mid-range-frequency tonal noise at the cost of broadband noise in high-frequency range, which is beneficial for the loudness of low weighting in the high-frequency range. Gwak et al [24] also reported that the fluctuation strength and the sharpness are a notable feature observed in the annoyance of UAV noise.…”
Section: Discussionsupporting
confidence: 68%
“…In terms of psychoacoustics, Merino-Martinez et al ( 2021) [21] presented a psychoacoustic metrics-based approach to evaluate the wind turbine acoustic performance of noise suppression measures, and pointed out the importance of the noise characteristics for the perceived annoyance, including the tonality, spectral content, and amplitude modulation. In fact, a series of studies have shown that the noise generated by rotorcrafts can cause human beings to be more annoyed than the traffic noises induced by other transportation sources because of the very specific noise characteristics of the drone propellers [9,[22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The wide variety of helicopter noise is pointed out as one of the main difficulties in the psycho-acoustics studies. Nevertheless, recently several studies improved the understanding of the perception of helicopter noise [2][3][4][5][6]. Thanks to the analysis of listening tests' results, they investigated the source of annoyance and linked it to the sound characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In industrial applications such as automotive, aviation, rail or consumer goods, tonality expresses the relative weight of the tonal components over their ambient frequency content. Tonality in rotary machines has become a research topic in terms of the psychoacoustic impact on humans in different fields, ranging from the aviation industry [25] to household equipment, such as vacuum cleaners [26].…”
Section: Introductionmentioning
confidence: 99%